Genomic insights into antimicrobial potential and optimization of fermentation conditions of pig-derived Bacillus subtilis BS21 - Wu, Di; Fu, Linglong; Cao, Yunhe; Dong, Na; Li, Defa (Frontiers in Microbiology, 2023)
Bacillus spp. have been widely used as probiotic supplements in animal feed as alternatives to antibiotics. In the present study, Bacillus subtilis strain BS21, which derived from pig feces, showed antimicrobial activities against a variety of animal pathogens, including Escherichia coli, Salmonella enterica Pullorum, Salmonella enterica Typhimurium, Citrobacter rodentium, Shigella flexneri and Staphylococcus aureus. We further analyzed the whole genome of strain BS21 and identified seven gene clusters involved in antimicrobial biosynthesis of secondary metabolites, including four nonribosomal peptides (bacillibactin, fengycin, surfactin and zwittermicin A), one ribosomal peptide (subtilosin A), one dipeptide (bacilysin) and one polyketide (bacillaene). Production of surfactin, fengycin, bacillibactin, bacilysin and bacillaene was detected by UHPLC-MS/MS in the supernatant of B. subtilis strain BS21. In addition, we optimized medium components and fermentation parameters for antimicrobial secondary metabolite production by BS21 using response surface methodology (RSM). The best medium formula of strain BS21 after optimization was corn flour 2%, soybean meal 1.7% and NaCl 0.5% with optimum culture parameters of initial pH 7.0, temperature 30ºC, rotating speed at 220 rpm for 26 h. Production of antimicrobial secondary metabolites of strain BS21 was increased by 43.4%. Our results provided valuable genomic information and suitable fermentation conditions of BS21, which enables further exploration of its antimicrobial mechanism and large-scale production. Strain BS21 can be used as a potential source of probiotics and alternative to antibiotics for animal production.